2023
DOI: 10.3390/life13030652
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Autoimmune Comorbidities in Microscopic Colitis and Inflammatory Bowel Diseases

Abstract: Background: Inflammatory bowel diseases (Crohn’s disease and ulcerative colitis) and microscopic colitis (lymphocytic and collagenous colitis) are immune-mediated diseases of the gastrointestinal tract, with distinct pathophysiology. Objective: We sought to compare the prevalence of autoimmune diseases between microscopic colitis (MC) and inflammatory bowel diseases (IBDs) in our patient cohorts in their medical history. Methods: We collected data from 611 patients (508 with IBD, 103 with MC). We recorded case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…As stated before, we did not find any connection between MC and AOSD, but our research revealed a possible link with Basedow’s disease. In an observational study, 75 patients with CC displayed concomitantly auto-immune disorders, most frequently Hashimoto thyroiditis, rheumatoid arthritis, lupus and Sjogren syndrome, while Basedow’s disease was reported in one case [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…As stated before, we did not find any connection between MC and AOSD, but our research revealed a possible link with Basedow’s disease. In an observational study, 75 patients with CC displayed concomitantly auto-immune disorders, most frequently Hashimoto thyroiditis, rheumatoid arthritis, lupus and Sjogren syndrome, while Basedow’s disease was reported in one case [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…This, more restrictive, algorithm yielded only 9 events, all occurring in reference individuals, and thus, a hazard ratio could not be computed. We also note that Saini et al (4) recently published an article concluding that the purported APinducing effects of many medications rely on limited evidence. We agree that monitoring events after reintroduction of certain medications would be a worthwhile The American Journal of GASTROENTEROLOGY…”
mentioning
confidence: 87%
“…Hence, regarding these comorbidities as time-varying covariates of AP risk may be preferable. Moreover, adjusting for other autoimmune diseases associated with AP (such as autoimmune pancreatitis, type 1 diabetes, and primary sclerosing cholangitis) as covariates would increase the reliability and credibility of the results (4).…”
mentioning
confidence: 99%